Detecting communities at high-risk of IUU fishing: networks of shadow encounters in Area 81 of the Western Central Pacific - Bichler, Gisela; Petrossian, Gohar A.; Viramontes, Kierston; Marteache, Nerea (Frontiers in Marine Science, 2024)
Introduction Illegal, unreported, and unregulated (IUU) fishing is a serious environmental crime with severe economic, social, and security implications. Efforts to monitor IUU fishing could be enhanced by using patterns of at-sea transshipment of fish to detect illicit subgroups. Methods Using data from Global Fishing Watch, this study investigates repeat transshipment events among vessels observed to operate in the U.N. FAO Area 81 during 2015-2021. Ship-to-ship transfer networks mapping potential encounters among 30 refrigerated cargo vessels (carriers) and 613 fishing vessels exhibit distinct communities that extend beyond this region. Results Highly central, carriers associated with open registries (flags of convenience) and exhibiting high operational deficiencies form networks that shadow the activities of national fleets. Discussion Observed between group linkages among vessels draw attention to these parallel trade currents embedding regional activity into the larger fishing industry, providing a focus for monitoring and conservation efforts.